Electrode precursor composition
By using the polymer-electrolyte gel matrix phase of the first polymer and the second polymer blend in a lithium-ion secondary battery, the problems of electrode structure instability and the safety hazards of liquid electrolytes are solved, and the battery performance and life are improved.
Patent Information
- Application Number
- CN202380057063.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-29
- Filing Date
- 2023-07-25
- Publication Date
- 2025-02-28
AI Technical Summary
During use, existing lithium-ion secondary batteries are prone to unstable electrode structure due to the dissolved polymer of liquid electrolyte, shortening the life of the battery cell. At the same time, the use of liquid electrolytes poses safety risks.
Using a polymer-electrolyte gel matrix phase containing a first polymer and a second polymer blend, the first polymer has a higher solubility in the liquid electrolyte than the second polymer, and a volume ratio of between 0.2 and 7, combining the electrochemically active material to form an electrode precursor composition.
A good balance of the electrode precursor composition during manufacturing and use is achieved, providing a higher electrolyte concentration to improve battery performance, while maintaining the stability of the electrode structure and extending the life of the battery cell.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to an electrode precursor composition for an alkali metal ion secondary battery cell, an electrode, a battery cell and an energy storage device made from the precursor composition, and a method for preparing an electrode for an alkali metal ion secondary battery cell. Background Art
[0002] Lithium-ion secondary batteries are the leading battery technology used today in applications ranging from small personal devices to electric vehicles. Lithium-ion batteries are favored for their high energy density and long cycle life. They contain multiple lithium-ion secondary battery cells, which are an example of an alkali metal ion secondary battery cell.
[0003] Traditionally, lithium-ion battery components, such as electrodes, are made by a solvent casting process that uses sacrificial solvents. This is an energy-expensive step, so a process that avoids the use of sacrificial solvents is needed.
[0004] Another major disadvantage of lithium-ion technology and other alkali metal ion secondary battery cell technologies is that liquid electrolytes are often used in the lithium-ion battery cells of the battery to provide conductivity of lithium ions in the battery cell between the solid, solvent-cast anode and cathode. This leads to safety issues because liquid electrolytes are often highly flammable. This is a particular problem for electric vehicles, where a collision with another vehicle may be relatively large and the resulting impact may cause battery damage and electrolyte ignition. This is also a problem for household devices, as a lithium-ion battery fire may cause property damage or serious injury.
[0005] One approach to avoid the use of sacrificial solvents and the need for liquid electrolytes within the battery cell is to prepare gel electrodes. These electrodes can be formed from a composition prepared by mixing the necessary components such as electrochemically active materials, polymers, and liquid electrolytes, and then heat treating the composition.
[0006] The choice of polymer used in the gel electrode can cause problems during operation of the battery cell. The gel electrode composition contains a small amount of liquid electrolyte to assist in the gelation of the polymer, so it is beneficial for the polymer to have a certain solubility in the electrolyte so that the gel can be formed more easily and the processability of the gel electrode is improved, reducing manufacturing costs. However, this in turn makes the final gel electrode more susceptible to dissolution in the electrolyte present between the electrodes in the final battery cell, reducing the operational life of the battery cell. In contrast, polymers with poor solubility in the electrolyte can ensure that once assembled, the gel electrode will not be degraded by the electrolyte present in the battery cell. However, due to the poor gelation between the polymer and the electrolyte, such electrodes are difficult to manufacture.
[0007] There is a need for gel electrode precursor compositions that are both easy to handle and provide strong electrodes that facilitate good battery cell life. Summary of the invention
[0008] The present invention generally relates to an electrode precursor composition for an alkali metal ion secondary battery cell, and more particularly to an electrode precursor composition comprising a polymer-electrolyte gel matrix phase comprising a polymer blend.
[0009] A first aspect of the present invention is an electrode precursor composition for an alkali metal ion secondary battery cell, comprising:
[0010] a polymer-electrolyte gel matrix phase comprising a blend of a first polymer, a second polymer different from the first polymer, and a liquid electrolyte; and
[0011] a dispersed phase comprising an electrochemically active material;
[0012] Wherein, the liquid electrolyte comprises an organic solvent and an alkali metal salt;
[0013] wherein the solubility of the first polymer in the liquid electrolyte is higher than the solubility of the second polymer in the liquid electrolyte; and
[0014] The volume ratio of the first polymer to the second polymer is 0.2 to 7.
[0015] The electrode precursor composition can be used as a precursor material for preparing a gel electrode.
[0016] The electrode precursor composition comprises a polymer-electrolyte gel matrix phase, which comprises a first polymer, a blend of a second polymer different from the first polymer, and a liquid electrolyte. The liquid electrolyte comprises an organic solvent, and the solubility of the first polymer in the liquid electrolyte is higher than the solubility of the second polymer in the liquid electrolyte. In this way, the electrode precursor composition provides a balance between processability (through the presence of a more soluble polymer) and durability during the use of the battery cell (through the presence of a less soluble polymer). The more soluble (first) polymer enables the formation of a more easily handled gel during the manufacture of the gel electrode. The less soluble (second) polymer is not easily dissolved into the battery electrolyte during the use of the battery cell, thus ensuring a good battery cell life.
[0017] In addition, the volume ratio of the first polymer to the second polymer is 0.2 to 7. Within this range, the polymer blend achieves a good balance of processability and durability.
[0018] Another benefit of the electrode precursor composition is that the concentration of the alkali metal salt in the entire composition is higher than that possible in the absence of the polymer blend. The higher salt concentration increases the conductivity of the gel electrode, improving the electrochemical performance of the battery cell. Due to the presence of the more soluble first polymer in the blend, a larger amount of liquid electrolyte can be incorporated into the electrode precursor composition, while the presence of the second polymer improves any detrimental effects on the stability of the electrode structure. A larger amount of liquid electrolyte means a higher salt concentration and thus improved electrode performance without any significant effect on the stability of the electrode structure.
[0019] Dissolution of the first polymer in the liquid electrolyte occurs at a temperature of at least 30°C, or at least 50°C, or at least 80°C, and forms a gel that is very stable at room temperature.
[0020] A second aspect of the present invention is an electrode for an alkali metal ion secondary battery cell, comprising:
[0021] a polymer-electrolyte gel matrix phase comprising a blend of a first polymer, a second polymer different from the first polymer, and a liquid electrolyte; and
[0022] a dispersed phase comprising an electrochemically active material;
[0023] Wherein, the liquid electrolyte comprises an organic solvent and an alkali metal salt;
[0024] wherein the solubility of the first polymer in the liquid electrolyte is higher than the solubility of the second polymer in the liquid electrolyte; and
[0025] The volume ratio of the first polymer to the second polymer is 0.2 to 7.
[0026] A third aspect of the present invention is a method of producing an electrode, comprising treating the electrode precursor composition according to the first aspect to form a film or a coating.
[0027] A fourth aspect of the present invention is an electrochemical secondary battery cell comprising the electrode according to the second aspect.
[0028] A fifth aspect of the invention is an electrochemical energy storage device comprising the electrochemical secondary battery cell according to the fourth aspect. DETAILED DESCRIPTION
[0029] The preferred and / or optional features of the present invention will now be described. Unless the context otherwise requires, any aspect of the present invention may be combined with any other aspect of the present invention. Any preferred and / or optional features of any aspect may be combined with any aspect of the present invention individually or in combination, unless the context otherwise requires.
[0030] In some embodiments, the electrochemically active material comprises 50 to 75 volume %, eg, 50 to 70 volume %, 50 to 69 volume %, 50 to 68 volume %, 55 to 68 volume %, 58 to 68 volume %, or 60 to 68 volume % of the electrode precursor composition.
[0031] In some embodiments, the electrochemically active material comprises 62 to 75 volume %, eg, 62 to 70 volume %, 62 to 69 volume %, 62 to 68 volume %, or 64 to 69 volume % of the electrode precursor composition.
[0032] In some embodiments, the dispersed phase further comprises a conductive additive. This may be a particulate conductive additive.
[0033] In some embodiments, the conductive additive comprises or consists of one or more forms of carbon. In some embodiments, the conductive additive comprises or consists of one or more of carbon black, graphite, and other forms of carbon. In some embodiments, the conductive additive comprises or consists of one or more of carbon black and graphite. In some embodiments, the conductive additive comprises or consists of carbon black. Examples of commercially available carbon black include Ketjen Black and Super C65.
[0034] In some embodiments, the conductive additive is present in an amount of 0.2 wt % to 2.5 wt %, such as 0.5 wt % to 2.5 wt %, based on the total weight of the electrode precursor composition.
[0035] In some embodiments, the conductive additive is present in an amount of 0.3 vol% to 2.5 vol%, e.g., 0.5 vol% to 2.5 vol%, 0.5 vol% to 2.4 vol%, 0.5 vol% to 2.3 vol%, 0.5 vol% to 2.2 vol%, 0.5 vol% to 2.1 vol%, or 0.9 vol% to 1.5 vol%, based on the total weight of the electrode precursor composition.
[0036] In some embodiments, the dispersed phase comprises 1.2 vol% to 4 vol% of the conductive additive, e.g., 1.2 vol% to 3.9 vol%, 1.2 vol% to 3.8 vol%, 1.2 vol% to 3.7 vol%, 1.2 vol% to 3.6 vol%, 1.2 vol% to 3.5 vol%, or 1.4 vol% to 2.0 vol%, based on the total volume of the dispersed phase.
[0037] In some embodiments, the dispersed phase comprises 96% to 99% by volume of the electrochemically active material, e.g., 97% to 98.9%, 97% to 98.8%, 97.5% to 99%, 98% to 99%, or 98.4% to 98.6% by volume, based on the total volume of the dispersed phase.
[0038] The dispersed phase may consist of an electrochemically active material and a conductive additive. In some embodiments, the dispersed phase consists of an electrochemically active material and carbon black.
[0039] In some embodiments, the polymer-electrolyte gel matrix phase comprises a mixture of a blend of first and second polymers and a liquid electrolyte, wherein the weight ratio of electrolyte:polymer blend is 2 to 10, such as 2 to 6.
[0040] In some embodiments, the electrode precursor composition includes the polymer blend in an amount of 2 to 10 vol %, such as 2 to 9 vol %, 2 to 8 vol %, 3 to 8 vol %, or 3 to 5 vol %, based on the total volume of the electrode precursor composition.
[0041] In some embodiments, the polymer-electrolyte gel matrix phase comprises the polymer blend in an amount of 5 to 30 vol %, e.g., 5 to 25 vol %, 8 to 24 vol %, 10 to 24 vol %, 10 to 23 vol %, 10 to 22 vol %, or about 10 to 15 vol %, based on the total volume of the polymer-electrolyte gel matrix phase.
[0042] In some embodiments, the polymer-electrolyte gel matrix phase comprises the liquid electrolyte in an amount of 70 to 95 vol %, such as 75 to 90 vol %, 85 to 90 vol %, or 87 to 89 vol %, based on the total volume of the polymer-electrolyte gel matrix phase.
[0043] In some embodiments, the electrode precursor composition includes the liquid electrolyte in an amount of 20 to 35 vol %, eg, 21 to 34 vol %, 22 to 33 vol %, 23 to 32 vol %, or 24 to 32 vol %, based on the total volume of the electrode precursor composition.
[0044] As described above, the present invention allows the amount of liquid electrolyte present to increase while maintaining good structural stability of the gel electrode. Therefore, in some embodiments, the liquid electrolyte constitutes at least 31% by volume of the electrode precursor composition, such as greater than 31% by volume, such as greater than 31.00% by volume, such as greater than 31% by volume to 35% by volume. Compositions containing a single type of polymer that provides the necessary structural stability cannot incorporate this level of electrolyte. In contrast, compositions containing a single type of polymer that can incorporate this level of electrolyte cannot provide the necessary structural stability, and the electrode will be degraded by the battery cell electrolyte during use, thereby shortening the life of the battery cell. The present invention allows higher levels of liquid electrolyte (and thus higher levels of alkali metal salts) in the gel electrode while maintaining good structural stability.
[0045] In some embodiments, the polymer-electrolyte gel matrix phase consists of a gelled polymer blend and a liquid electrolyte.
[0046] In some embodiments, the liquid electrolyte comprises or consists of an organic solvent comprising one or more cyclic or linear carbonate compounds. In some embodiments, the solvent comprises one or more cyclic carbonate compounds. In some embodiments, the solvent comprises one or more of the following: ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl carbonate-methyl ester, butylene carbonate, vinylene carbonate, fluoroethylene carbonate, fluoropropylene carbonate and γ-butyrolactone.
[0047] In some embodiments, the solvent comprises one or more of ethylene carbonate, propylene carbonate, vinylene carbonate, and fluoroethylene carbonate. In some embodiments, the solvent comprises or consists of a mixture of ethylene carbonate, propylene carbonate, vinylene carbonate, and fluoroethylene carbonate.
[0048] In some embodiments, the solvent comprises a blend of at least two different compounds, such as at least three or at least four different compounds. In some embodiments, the solvent comprises a blend of at least two different organic carbonate compounds, such as at least three or at least four different organic carbonate compounds.
[0049] In some embodiments, the solvent comprises ethylene carbonate in an amount of at least 50% by weight, such as at least 55% by weight, at least 60% by weight, or at least 65% by weight, based on the total weight of the solvent. In some embodiments, the solvent comprises ethylene carbonate in an amount of up to 80% by weight, such as up to 75% by weight or up to 70% by weight, based on the total weight of the solvent. In some embodiments, the solvent comprises ethylene carbonate in an amount of 50 to 80% by weight, such as 65 to 75% by weight, based on the total weight of the solvent.
[0050] In some embodiments, the solvent comprises propylene carbonate in an amount of at least 10 wt %, such as at least 15 wt %, at least 20 wt %, or at least 22 wt %, based on the total weight of the solvent. In some embodiments, the solvent comprises propylene carbonate in an amount of up to 35 wt %, such as up to 30 wt % or up to 25 wt %, based on the total weight of the solvent. In some embodiments, the solvent comprises propylene carbonate in an amount of 10 to 35 wt %, such as 20 to 25 wt %, based on the total weight of the solvent.
[0051] In some embodiments, the solvent comprises vinylene carbonate in an amount of at least 1 wt %, such as at least 2 wt %, at least 3 wt %, or at least 4 wt %, based on the total weight of the solvent. In some embodiments, the solvent comprises vinylene carbonate in an amount of up to 10 wt %, such as up to 8 wt % or up to 6 wt %, based on the total weight of the solvent. In some embodiments, the solvent comprises vinylene carbonate in an amount of 1 to 10 wt %, such as 3 to 6 wt %, based on the total weight of the solvent.
[0052] In some embodiments, the solvent comprises fluoroethylene carbonate in an amount of at least 1 wt %, such as at least 1.5 wt %, at least 2 wt %, or at least 2.5 wt %, based on the total weight of the solvent. In some embodiments, the solvent comprises fluoroethylene carbonate in an amount of up to 10 wt %, such as up to 5 wt %, or up to 3 wt %, based on the total weight of the solvent. In some embodiments, the solvent comprises fluoroethylene carbonate in an amount of 1 to 10 wt %, such as 2 to 4 wt %, based on the total weight of the solvent.
[0053] In some embodiments, the liquid electrolyte further comprises one or more lithium salts. Examples of suitable lithium salts include LiPF6, LiBF4, lithium bis(fluorosulfonyl)imide (LiFSI), and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI).
[0054] In some embodiments, the liquid electrolyte includes one or more lithium salts selected from the following: LiPF6, LiBF4, lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and 2-trifluoromethyl-4,5-dicyanoimidazole lithium (LiTDI). In some embodiments, the liquid electrolyte comprises a solvent and a lithium salt component as described above, and the lithium salt component comprises or consists of one or more lithium salts selected from LiPF6, LiBF4, LiFSI, LiTFSI and LiTDI. In some embodiments, the liquid electrolyte comprises a solvent and a lithium salt component as described above, and the lithium salt component comprises or consists of one or more lithium salts selected from LiFSI and LiTDI.
[0055] In some embodiments, the liquid electrolyte comprises or consists of an organic solvent and an alkali metal salt; wherein the organic solvent consists of one or more of the following: ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl-methyl carbonate, butylene carbonate, vinylene carbonate, fluoroethylene carbonate, fluoropropylene carbonate and γ-butyrolactone; the alkali metal salt consists of one or more of LiPF6, LiBF4, LiFSI, LiTFSI and LiTDI. In some embodiments, the liquid electrolyte comprises or consists of an organic solvent and an alkali metal salt; wherein the organic solvent consists of one or more of ethylene carbonate, propylene carbonate, vinylene carbonate and fluoroethylene carbonate; the alkali metal salt consists of one or more of LiFSI and LiTDI.
[0056] In some embodiments, the liquid electrolyte comprises a mixture of at least two different lithium salts. In some embodiments, the solvent comprises a blend of at least two different organic carbonate compounds, such as at least three or at least four different organic carbonate compounds, and the liquid electrolyte comprises a mixture of at least two different lithium salts.
[0057] In some embodiments, the concentration of the lithium salt in the organic solvent is at least 10 wt %, such as at least 11 wt %, at least 12 wt %, at least 13 wt %, at least 14 wt %, or at least 15 wt %, based on the total weight of the liquid electrolyte. In some embodiments, the concentration of the lithium salt in the organic solvent is up to 50 wt %, such as up to 40 wt %, up to 30 wt %, up to 25 wt %, or up to 24 wt %, based on the total weight of the liquid electrolyte.
[0058] In some embodiments, the concentration of the lithium salt in the organic solvent is 10 to 30 wt %, eg, 12 to 25 wt % or 15 to 25 wt %, based on the total weight of the liquid electrolyte.
[0059] In some embodiments, the polymer-electrolyte gel matrix phase comprises 20% to 50% by volume of the electrode precursor composition, e.g., 25% to 45% by volume, 28% to 42% by volume, 30% to 40% by volume, 31% to 49% by volume, or 32% to 48% by volume.
[0060] Based on the specific multimodal particle size distribution of the active material, the benefits of the present invention can be realized for any active material that may be present in the electrode composition. The skilled person will be aware of the large number of possible electrochemically active materials that can be used in the present invention, including cathode active materials (also known as positive electrode active materials) and anode active materials (also known as negative electrode active materials).
[0061] The electrochemically active material is a particulate material, ie a material consisting of a plurality of discrete particles. The particles may include primary particles and / or secondary particles formed by the aggregation of a plurality of primary particles.
[0062] In some embodiments, the electrochemically active material is a cathode active material.
[0063] In some embodiments, the positive electrode active material is a lithium transition metal oxide material. In some embodiments, the positive electrode active material is a lithium transition metal oxide material, which comprises a mixed metal oxide of lithium and one or more transition metals, and optionally further comprises one or more additional non-transition metals. In some embodiments, the positive electrode active material is a lithium transition metal oxide material comprising lithium and one or more transition metals selected from nickel, cobalt and manganese. In some embodiments, the positive electrode active material is selected from lithium cobalt oxide (LCO), lithium manganese oxide (LMO), lithium nickel cobalt oxide (NCO), aluminum-doped lithium nickel cobalt oxide (NCA), lithium nickel manganese cobalt oxide (NMC), lithium nickel oxide (LNO), lithium nickel manganese oxide (LNMO), lithium iron phosphate (LFP), lithium manganese iron phosphate (LFP) and lithium nickel vanadate (LNV) One or more. In some embodiments, the positive electrode active material is lithium nickel manganese cobalt oxide (NMC), optionally doped with another metal, such as aluminum.
[0064] In some cases, the electrochemically active material may include carbon, suitably graphite, graphene, or a blend of carbon and silicon oxide.
[0065] Such electrochemically active materials are commercially available or can be made by methods known to those skilled in the art, for example by precipitation of a mixed metal hydroxide intermediate from a reaction mixture containing various precursor metal salts, followed by calcination to form a mixed metal oxide, and optionally lithiation to incorporate lithium into the oxide.
[0066] The electrochemically active material may be undoped or uncoated, or may include one or more dopants and / or coatings. For example, the electrochemically active material may be doped with a small amount of one or more metallic elements. The electrochemically active material may include a carbon coating on the surface of the material particles.
[0067] In some embodiments, the electrochemically active material is a negative electrode active material.
[0068] In some embodiments, the electrochemically active material has a bimodal particle size distribution.
[0069] The polymer-electrolyte gel matrix phase comprises a gel matrix formed by swelling of the swellable polymer blend as the polymer blend absorbs liquid electrolyte. Thus, the polymer-electrolyte gel matrix phase comprises a gel containing the polymer blend and the absorbed liquid electrolyte.
[0070] The polymer blend includes a blend of a first polymer and a second polymer, wherein the solubility of the first polymer in the liquid electrolyte is higher than the solubility of the second polymer in the liquid electrolyte.
[0071] Those skilled in the art will appreciate that the relative solubility of the first and second polymers in the liquid electrolyte will depend on the choice of liquid electrolyte and / or the choice of liquid electrolyte components (eg, solvent).
[0072] Typically, the presence of the (more soluble) first polymer is to improve the processability of the electrode precursor composition, as it has excellent gel-forming properties. On the other hand, the (less soluble) second polymer performs a structural function in the final gel electrode and is present despite its reduced gel-forming ability due to the improved structural properties it provides.
[0073] In some embodiments, the first polymer exhibits spontaneous dissolution in the liquid electrolyte at room temperature. Depending on the polymer, this may be a very slow process, but in some embodiments, exposing the liquid electrolyte to the polymer at room temperature without any specific mixing results in the formation of a gel.
[0074] In some embodiments, the first polymer requires additional energy input to initiate dissolution, but the result is a material that is in a very stable homogeneous state at room temperature. In some embodiments, at elevated temperatures (e.g., at or above 30° C., at or above 50° C., or at or above 80° C.), dissolution of the first polymer in the liquid electrolyte is rapid and forms a very stable gel at room temperature.
[0075] The stability of gels can be assessed in a number of ways:
[0076] • Visual assessment will show a single-phase material that is a stable gel with no obvious liquid-rich phase on the surface;
[0077] • Optical evaluation by microscopy etc. will not show any signs of phase separation;
[0078] • Further analytical evaluation, for example by DSC, spectroscopic methods including FTIR, RAMAN or EDX or x-ray diffraction, will show a homogeneous single phase mixture.
[0079] In some embodiments, the second polymer has no tendency to swell or dissolve in the liquid electrolyte at elevated temperatures.
[0080] In some embodiments, the second polymer does not show an apparent change in physical state when exposed to a liquid electrolyte at elevated temperatures, even when high shear mixing techniques are used. This can be confirmed by visual assessment, which will indicate an unchanged polymer when exposed to the liquid electrolyte. In addition, a DSC of the mixture may show an endothermic melting peak at the same temperature as the base polymer, indicating that the crystalline polymer phase in the material has not changed after exposure to the liquid electrolyte.
[0081] In some embodiments, the second polymer shows a partial tendency to swell or dissolve in the liquid electrolyte at elevated temperatures. The second polymer may swell slightly in the liquid electrolyte in this manner, but it may be difficult to visually observe. In this case, a DSC measurement of the mixture may show that the endothermic melting peak of the polymer in the mixture is different from the endothermic melting peak of the base polymer, indicating a change in crystallinity when exposed to the liquid electrolyte.
[0082] In some embodiments, the second polymer may exhibit significant swelling and plasticization within the liquid electrolyte, but may not absorb all of the liquid electrolyte in the desired amount. Visual assessment will reveal this behavior by indicating free liquid surrounding the gel.
[0083] In some embodiments, the second polymer may swell and plasticize with the entire amount of liquid electrolyte at elevated temperature, but evaluation of the gel in this state at this temperature may indicate an inhomogeneous mixture. For example, rheological evaluation of such a mixture may be difficult to measure, or noisy, indicating an inhomogeneous composition or phase separation.
[0084] In some embodiments, the second polymer may exhibit the ability to swell or dissolve in a liquid electrolyte at elevated temperatures, but the mixture may be unstable at room temperature. A polymer such as this polymer may fully swell and plasticize with a liquid electrolyte at elevated temperatures, but when returned to room temperature it will exhibit behavior indicating that it is inhomogeneous or unstable. For example, a visual assessment of such a material may indicate that liquid is rejected from a gel mass, as droplets formed on the surface, or aggregated around a bulk material.
[0085] In some embodiments, the first and second polymers are different from each other and are each independently selected from poly(ethylene dimethacrylate), poly(ethylene diacrylate), poly(propylene dimethacrylate), poly(propylene diacrylate), poly(methyl methacrylate) (PMMA), poly(acrylonitrile) (PAN), polyurethane (PU), poly(vinylidene fluoride) (PVdF), poly(vinylidene fluoride-co-hexafluoropropylene) (PvDF-HFP), poly(ethylene oxide) (PEO), poly(ethylene glycol dimethyl ether), poly(ethylene glycol diethyl ether), polychlorotrifluoroethylene (PCTFE), polytetrafluoroethylene (PTFE), poly[bis(methoxyethylene)] [(4-styrenesulfonyl)(trifluoromethanesulfonyl)imide-co-methoxy-polyethylene glycol acrylate]] (Li[PSTFSI-co-MPEGA]), sulfonated polyphenylene oxide (PPO), N,N-dimethylacrylamide (DMAAm), lithium 2-acrylamido-2-methyl-1-propane sulfonate (LiAMPS), poly(2-acrylamido-2-methylpropane sulfonate-co-vinyltriethoxysilane), polyethylene oxide (PEO) / poly(lithium sorbate), PEO / poly(lithium mucate), PEO / [poly(lithium sorbate)+BF3], PEO copolymers, PEO terpolymers, and NIPPON SHOKUBAI® polymers.
[0086] The first polymer can be a polymer selected from the above list, and the second polymer can be a different polymer selected from the above list, provided that the solubility of the first polymer in the liquid electrolyte is higher than the solubility of the second polymer in the liquid electrolyte. Each of the first and second polymers can be formulated from two or more polymers that meet the solubility requirements of each of the first and second polymers. For example, the two polymers can be from the same chemical group, such as PVDF-HFP, but the ratio of the chemical groups, or other characteristics of the polymers, such as molecular weight, or the order of the copolymer groups are different enough to make the two polymers exhibit the relative properties of the first and second polymers as described above.
[0087] In some embodiments, the first polymer is selected from polymethyl methacrylate (PMMA) and polyethylene glycol (PEG). In other embodiments, the first polymer is selected from PVDF-HFP.
[0088] In some embodiments, the second polymer is polyvinylidene fluoride (PVDF). In other embodiments, the second polymer is functionalized PVDF, also known as modified PVDF, an example of which is PVDF-HFP. However, the skilled person will be aware of alternative functionalized or modified PVDF polymers.
[0089] In some embodiments, the first polymer is selected from polymethyl methacrylate (PMMA) and polyethylene glycol (PEG); the second polymer is polyvinylidene fluoride (PvDF). In some embodiments, the first polymer is polymethyl methacrylate (PMMA) and the second polymer is polyvinylidene fluoride (PvDF). In some embodiments, the first polymer is poly(vinylidene fluoride-co-hexafluoropropylene) (PvDF-HFP) and the second polymer is poly(vinylidene fluoride) (PVdF).
[0090] In some embodiments, the volume ratio of the first polymer to the second polymer is 0.75 to 0.85. Such a ratio provides a particularly stable and processable composition.
[0091] In some embodiments, the electrode precursor composition is for a lithium ion secondary electrochemical cell. In some embodiments, the electrode precursor composition is a cathode precursor composition.
[0092] A second aspect of the present invention is an electrode for an alkali metal ion secondary battery cell, comprising:
[0093] a polymer-electrolyte gel matrix phase comprising a blend of a first polymer and a second polymer different from the first polymer and a liquid electrolyte; and
[0094] a dispersed phase comprising an electrochemically active material;
[0095] Wherein, the liquid electrolyte comprises an organic solvent and an alkali metal salt;
[0096] wherein the solubility of the first polymer in the liquid electrolyte is higher than the solubility of the second polymer in the liquid electrolyte; and
[0097] The volume ratio of the first polymer to the second polymer is 0.2 to 7.
[0098] In some embodiments, the electrode is produced by processing the electrode precursor composition according to the first aspect to form a film.
[0099] In some embodiments, the electrode is an extruded electrode. In other embodiments, the electrode is a hot rolled electrode. In other embodiments, the electrode is prepared by die extruding the electrode precursor composition according to the first aspect to form a film.
[0100] In some embodiments, the electrode is a cathode.
[0101] All compositional options and preferences described above for the electrode precursor composition of the first aspect apply equally to the electrode of the second aspect, including the identity and relative amounts of the various components of the composition, which are not altered during processing of the precursor composition into an electrode.
[0102] In some embodiments, processing comprises heat treatment or extrusion.
[0103] In some embodiments, the thermal treatment comprises passing the electrode precursor composition through a roller assembly at a temperature of at least 50° C., e.g., at least 60° C., at least 70° C., at least 80° C., at least 90° C., or at least 100° C. In some embodiments, the thermal treatment comprises passing the electrode precursor composition through a roller assembly at a temperature of up to 150° C., e.g., up to 140° C., or up to 130° C. In some embodiments, the thermal treatment comprises passing the electrode precursor composition through a roller at a temperature of 50° C. to 150° C., e.g., 60° C. to 150° C., 70° C. to 150° C., 80° C. to 150° C., 80° C. to 140° C., 90° C. to 140° C., 100° C. to 140° C., or 110° C. to 130° C.
[0104] The roller assembly may include two rollers separated by a small distance so that the electrode is pressed into a thin film as it passes over the rollers.
[0105] In some embodiments, the heat treatment comprises extruding the electrode. In some embodiments, the heat treatment comprises extruding the electrode using an extrusion device, the extrusion device comprising one or more screw feed sections and an extrusion die. In some embodiments, the temperature of the die is at least 50°C, such as at least 60°C, at least 70°C, at least 80°C, at least 90°C or at least 100°C. In some embodiments, the temperature of the die is up to 150°C, such as up to 140°C or up to 130°C. In some embodiments, the temperature of the die is at least 50°C to 150°C, such as 60°C to 150°C, 70°C to 150°C, 80°C to 150°C, 80°C to 140°C, 90°C to 140°C, 100°C to 140°C or 110°C to 130°C.
[0106] In some embodiments, the thickness of the electrode is less than 150 μm, such as less than 100 μm, less than 90 μm, less than 80 μm, or less than 70 μm. In some embodiments, the thickness of the electrode is 40 to 150 μm, such as 40 to 100 μm, 40 to 90 μm, 40 to 80 μm, 40 to 70 μm, or 50 to 70 μm.
[0107] In some embodiments, the electrode has a thickness of 40 to 150 μm, such as 40 to 100 μm, 40 to 90 μm, 40 to 80 μm, 40 to 70 μm, or 50 to 70 μm.
[0108] In some embodiments, the electrode has a porosity of less than about 5% by volume. In some cases, the porosity of the electrode is less than 5% by volume, less than 3% by volume, or less than 2% by volume. In other words, the volume density of the electrode can be at least 95% of the density of a completely non-porous electrode, suitably at least about 97% or 98%.
[0109] In some cases, the extruded electrode may form part of an extruded monolith that includes one or more other layers present in an electrochemical cell. For example, the monolith may include a separator layer, and / or may include another electrode (i.e., the extruded monolith may include a cathode and an anode). Different layers may be coextruded and have different compositions from each other.
[0110] A third aspect of the invention provides an electrochemical secondary battery cell comprising an electrode according to the second aspect. The battery cell may be an alkali metal ion secondary battery cell, such as a sodium ion secondary battery cell or a lithium ion secondary battery cell. Preferably, the battery cell is a lithium ion secondary battery cell. In some embodiments, the electrochemical secondary battery cell comprises a first electrode according to the second aspect, wherein the first electrode is a cathode, and a second electrode according to the second aspect, wherein the second electrode is an anode, and an electrolyte between the cathode and the anode. In some embodiments, the electrochemical secondary battery cell comprises an electrode according to the second aspect, which is stacked with a current collector such as a metal foil.
[0111] A fourth aspect of the present invention provides an electrochemical energy storage device comprising an electrochemical secondary battery cell according to the third aspect. In some embodiments, the electrochemical energy storage device is a battery. In some embodiments, the electrochemical energy storage device is a lithium-ion battery.
[0112] A fifth aspect of the present invention provides a method for preparing an electrode for an alkali metal ion secondary battery cell, comprising:
[0113] mixing a polymer, an electrolyte and an electrochemically active material to form an electrode precursor composition according to the first aspect; and
[0114] The electrode precursor composition is heat treated to form an electrode film.
[0115] In some embodiments, the electrode film has a thickness of 500 to 700 μm.
[0116] In some embodiments, the method further comprises cutting the electrode film to form electrodes of predetermined dimensions.
[0117] In some embodiments, the method further includes performing a second heat treatment step on the cut film to reduce the thickness of the film to a range of 50 to 70 μm.
[0118] In some embodiments, the temperature during heat treatment is 100 to 140°C.
[0119] Example
[0120] For all samples tested, the active material, conductive carbon, polymer and electrolyte were first weighed and mixed by hand until the mixture was uniform and free of lumps. The mixture was then fed into a twin-screw extruder with three mixing zones at multiple intervals. The body of the twin-screw extruder was maintained at 120 degrees on the mixing zone, with a 40-degree tilt starting from the input port and dropping to 80 degrees at the outlet. After the material was added to the twin-screw extruder, it was collected as a granular mixture.
[0121] This granular mixture was then rolled into a film. The precursor material was sandwiched between two sheets of polyester film and passed through a rolling mill at 120°C, with the roll gap set to ensure that the material was pressed to a thickness of 600 μm.
[0122] This 600 μm thick precursor film was then cut into 500 mm x 10 mm to evaluate the ability to form thin films. This portion of the film was then fed into a hot roller assembly to produce a film of the target thickness, typically 50-70 μm depending on the formulation.
[0123] The gel electrode precursor composition was prepared according to the composition shown in Table 1:
[0124] Table 1:
[0125]
[0126] Electrolytes A and B have the following compositions:
[0127]
[0128] Each electrode precursor composition in Table 1 was formed into a gel electrode film by the above method.
[0129] The gel electrode formed from the composition of Example 1 had a high concentration of electrolyte and exhibited good cohesion, good adhesion, and good liquid retention.
[0130] The gel electrode formed from the composition of Example 2 also had a high concentration of electrolyte and exhibited good cohesion, good adhesion, and good liquid retention.
[0131] The gel electrode formed from the composition of Comparative Example 1 had a lower electrolyte concentration than that of Examples 1 or 2. It was not possible to form a stable, processable composition having an electrolyte content equivalent to that of Examples 1 or 2.
[0132] This shows that including a primary polymer with solubility in the material composition enables the use of a higher concentration of electrolyte. In this case, PVDF-HFP Grade 2 is the primary polymer in Electrolyte A, but a secondary polymer in Electrolyte B. Therefore, in the case of Examples 1 and 2, it is necessary to include PMMA Grade 1 as the primary polymer in the formulation.
[0133] Comparative Example 2 The composition can be processed into an electrode under some conditions, but the result is an electrode with observable defects. Liquid separates from the electrode during hot rolling. The electrode contains structural defects and a higher porosity than expected. When tested in a battery cell under standard conditions, the current collector is often damaged. This indicates that the secondary polymer alone produces an unprocessable film.
[0134] When made into a film, the comparative example 3 composition showed good electrolyte retention and easy handling, but the film was sticky and left residue on the reverse film backing, indicating poor cohesion. A streak pattern was observed in the material, which was evidence of liquid flowing through the film, indicating poor structural robustness. The cathode made from this composition and tested in a battery cell under standard conditions showed poor stability due to the dissolution of the PMMA polymer. This shows that the primary polymer alone is not sufficient to ensure the stability of the electrode
[0135] New Example
[0136] This is to demonstrate that PVDF-HFP can be considered as both a primary polymer and a secondary polymer.
[0137]
[0138] Electrolyte C composition:
[0139]
[0140] Example 4 showed a membrane that could be processed to the target thickness and was shown to be able to retain the electrolyte during processing. However, further evaluation of the membrane showed that the cohesion and adhesion of the membrane were poor. In this case, the poor structural properties of the membrane made it unusable as an electrode.
[0141] Example 5 was shown to be processable into a film of target thickness and was shown to be able to retain electrolyte during processing and also was shown to have good cohesion and adhesion.
Claims
1. An electrode precursor composition for an alkali metal ion secondary battery cell, comprising: a polymer-electrolyte gel matrix phase comprising a blend of a first polymer and a second polymer different from the first polymer and a liquid electrolyte; and a dispersed phase comprising an electrochemically active material; Wherein, the liquid electrolyte comprises an organic solvent and an alkali metal salt; wherein the solubility of the first polymer in the liquid electrolyte is higher than the solubility of the second polymer in the liquid electrolyte; and The volume ratio of the first polymer to the second polymer is 0.2 to 7.
2. The electrode precursor composition according to claim 1, wherein The first polymer is selected from polymethyl methacrylate (PMMA), polyethylene glycol (PEG) and PVDF-HFP.
3. The electrode precursor composition according to claim 1 or 2, wherein The second polymer is polyvinylidene fluoride (PvDF), which includes copolymers of PVDF.
4. An electrode precursor composition according to any one of the preceding claims, wherein The liquid electrolyte is at least 31 volume % of the electrode precursor composition.
5. An electrode precursor composition according to any one of the preceding claims, wherein The volume ratio of the first polymer to the second polymer is 0.75 to 0.
85.
6. An electrode precursor composition according to any one of the preceding claims, wherein The electrochemically active material is a positive electrode active material.
7. The electrode precursor composition according to claim 6, wherein The electrochemically active material is a lithium transition metal oxide material.
8. An electrode precursor composition according to any one of the preceding claims, wherein The dispersed phase also includes a conductive additive.
9. The electrode precursor composition according to claim 8, wherein The conductive additive includes one or more of carbon black and graphite.
10. The electrode precursor composition according to claim 8 or 9, wherein The conductive additive is present in an amount of 0.2 wt % to 2.5 wt % based on the total weight of the electrode precursor composition.
11. An electrode precursor composition according to any one of the preceding claims, wherein The organic solvent comprises one or more cyclic or linear carbonate compounds.
12. An electrode precursor composition according to any one of the preceding claims, wherein The organic solvent comprises one or more of the following: ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl-methyl carbonate, butylene carbonate, vinylene carbonate, fluoroethylene carbonate, fluoropropylene carbonate and γ-butyrolactone.
13. An electrode precursor composition according to any one of the preceding claims, wherein The alkali metal salt includes one or more of the following: LiPF6, LiBF4, lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), and lithium 2-trifluoromethyl-4,5-dicyanoimidazole (LiTDI).
14. An electrode precursor composition according to any one of the preceding claims, wherein The concentration of the lithium salt in the organic solvent is 10 to 30 wt % based on the total weight of the liquid electrolyte.
15. An electrode precursor composition according to any one of the preceding claims, wherein The electrode precursor composition comprises 50 to 75 volume % of the electrochemically active material based on the total volume of the composition.
16. An electrode precursor composition according to any one of the preceding claims, wherein The electrochemically active material comprises at least 60 volume % of the electrode precursor composition.
17. An electrode precursor composition according to any one of the preceding claims, wherein The electrode precursor composition comprises 20 volume % to 50 volume % of the polymer-electrolyte gel matrix phase based on the total volume of the composition.
18. An electrode precursor composition according to any one of the preceding claims, wherein The polymer-electrolyte gel matrix phase comprises 5 to 30 volume % of the polymer based on the total volume of the polymer-electrolyte gel matrix phase.
19. An electrode precursor composition according to any one of the preceding claims for use in a lithium ion secondary electrochemical cell.
20. An electrode precursor composition according to any one of the preceding claims, wherein Dissolution of the first polymer in the liquid electrolyte occurs at a temperature of at least 30°C, or at least 50°C, or at least 80°C, and forms a gel that is very stable at room temperature.
21. An electrode for an alkali metal ion secondary battery cell, comprising: a polymer-electrolyte gel matrix phase comprising a blend of a first polymer and a second polymer different from the first polymer and a liquid electrolyte; and a dispersed phase comprising an electrochemically active material; Wherein, the liquid electrolyte comprises an organic solvent and an alkali metal salt; wherein the solubility of the first polymer in the liquid electrolyte is higher than the solubility of the second polymer in the liquid electrolyte; and The volume ratio of the first polymer to the second polymer is 0.2 to 7.
22. The electrode according to claim 21, produced by processing the electrode precursor composition according to any one of claims 1 to 21 to form a film or a coating.
23. The electrode according to claim 22, wherein The treatment includes heat treatment or extrusion.
24. The electrode according to claim 23, wherein The heat treatment includes passing the electrode precursor composition through a roller assembly at a temperature of at least 50°C, at least 60°C, at least 70°C, at least 80°C, at least 90°C, or at least 100°C.
25. A method of producing an electrode comprising treating an electrode precursor composition according to any one of claims 1 to 21 to form a film or coating.
26. An electrochemical secondary battery cell comprising an electrode according to any one of claims 21-25.
27. An electrochemical energy storage device comprising the electrochemical secondary battery cell according to claim 26.